MRI findings in patients with psychogenic non‐epileptic seizures: Prevalence, distribution, and classification of the findings. A single tertiary epilepsy center experience - Aleix Jareno‐Badenas; Mario Matute‐González; Luis Pintor; Estefanía Conde‐Blanco; Mar Carreño; Xavier Setoain; Camilo Pineda; Fernando Diego Choque‐Chávez; Tomás Fernández; Núria Bargalló; Sofía González‐Ortiz (Epilepsia Open)
Abstract Objective Psychogenic non‐epileptic seizures (PNES) mimic epileptic seizures without electroencephalographic correlation. Although classified as psychiatric disorders, their neurobiological or structural basis remains unclear. This study aimed to assess the prevalence and characteristics of MRI abnormalities in patients with PNES and those with comorbid epilepsy, compared to the general population, to enhance radiological evaluation and management. Method We retrospectively identified patients with a definitive diagnosis of PNES, evaluated in the refractory epilepsy unit of our tertiary epilepsy center. Patients were classified into two groups according to their comorbidity with epilepsy (PNES and PNES+). The MRI findings were evaluated and classified by two radiologists, who reported the category of the findings, laterality, and location. The two groups were compared using the chi‐square test, as well as the frequencies of findings in the general population extracted from the literature. Results Forty‐six patients fulfilled the inclusion criteria. Thirty females and 16 males. MRI findings were present in 25/35 (71.4%) patients in the PNES group and 9/11 (81.8%) In the PNES + group, showing statistically significant differences in the frequency of findings with the general population (8.4–28.1%). Significance MRI anomalies are common in PNES patients and even more prevalent in complex cases referred to epilepsy units, underscoring the necessity of correlating MRI findings with clinical‐electrical patterns. Plain Language Summary In this article, we observed a higher frequency of cerebral magnetic resonance findings in patients with psychogenic non‐epileptic seizures than in the general population. We also observed a higher frequency of this pathology among women, as well as right cerebral hemisphere affections. The exposed findings suggest a potential structural basis of this pathology. This hypothesis requires confirmation with larger studies.